DWI of the prostate: Comparison of a faster diagonal acquisition to standard three‐scan trace acquisition. Issue 6 (16th March 2017) - Corcuera‐Solano, Idoia; Wagner, Mathilde; Hectors, Stefanie; Lewis, Sara; Titelbaum, Nicholas; Stemmer, Alto; Rastinehad, Ardeshir; Tewari, Ashutosh; Taouli, Bachir
Abstract : Purpose: To compare a faster diagonal diffusion‐weighted imaging (d‐DWI) to conventional three‐scan trace DWI (t‐DWI) acquisition for prostate magnetic resonance imaging (MRI) in terms of image quality, tumor detection/conspicuity, Prostate Imaging Reporting and Data System (PI‐RADS) characterization, quantitative estimated signal‐to‐noise ratio (eSNR), and apparent diffusion coefficient (ADC) measurement. Patients and Methods: A total of 34 consecutive men with suspected prostate cancer (PCa) who underwent 3T MRI of the prostate were assessed. MRI included t‐DWI and d‐DWI (using b‐values of 50, 1000, and 1600 s/mm 2, number of averages 1/5/10 for t‐DWI vs. 2/8/14 for d‐DWI, acquisition time 6:21 min vs. 4:17 min, respectively). Two independent observers evaluated image quality, including image sharpness, anatomic distortion, and artifacts on a 5‐point scale (1–5) and assessed tumor detection, conspicuity, and PI‐RADS classification with both DWI sequences. eSNR and ADC were measured in the peripheral zone (PZ), transitional zone (TZ), and detected tumors. Data was compared using paired Wilcoxon signed rank tests and McNemar test. Coefficients of variations (CV) between ADC obtained with both sequences were calculated. Results: Significantly fewer artifacts were observed on d‐DWI at b 1600 for observer 2 ( P < 0.01), while the other image quality scores were equivalent for both sequences. eSNR was lower with d‐DWI vs. t‐DWI in PZ and TZ for b 1000 ( P < 0.01 and P  = 0.03, respectively) and b 1600 ( P < 0.01 for both). ADC reproducibility between sequences was excellent (CV <10%). No significant differences were found for tumor detection ( P ≥ 0.25), conspicuity ( P ≥ 0.12), or PI‐RADS classification ( P ≥ 0.10). Conclusion: d‐DWI can provide a substantial reduction in acquisition time (∼30%) while maintaining equivalent tumor detection, PI‐RADS score, image quality, and ADC values. Level of Evidence: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2017;46:1767–1775.